Strategi Pengembangan Sumber Daya Insani Berbasis Nilai IslamPada Takmir Masjid Baitul Mukhlisin Ponorogo - Putra Rizki Julianto; Aji Damanuri (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
The strategy for developing Islamic value–based human resources (SDI) within the Takmir of Masjid Baitul Mukhlisin. As a religious institution, the mosque holds a strategic role not only as a place of worship but also as a center for education and community empowerment. However, human resource management in many mosques still faces several challenges, such as limited managerial competence, a lack of training, and the suboptimal internalization of Islamic values in the work ethics of the management. This study uses a qualitative approach with a case study method. Data were obtained through in-depth interviews, observations, and documentation of takmir activities. The analysis was carried out using the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing. The findings show that human resource development at Masjid Baitul Mukhlisin has not been systematically implemented and still requires comprehensive improvements in terms of planning, training, and performance evaluation. The integration of Islamic Human Resource Management theory (Veithzal Rivai, 2005), Human Resource Development theory (Handoko & Dessler), and Islamic Values in Management theory (Beekun, 1997) indicates that the application of the values of amanah, ihsan, adl, shura, and ikhlas is crucial in shaping the character, professionalism, and responsibility of mosque administrators. Implementing Islamic value–based human resource development strategies can enhance the effectiveness of mosque management and strengthen congregational trust. Thus, strengthening SDI grounded in Islamic values becomes a key for mosques to optimally function as centers of worship, education, and community empowerment that embody civility and blessings.